La ciudad rota: el México miserable de Luis Buñuel y Guillermo Fadanelli - Gamboa Sánchez, Bernardo (Revista de Filología Románica, 2011)
The following article compares Luis Buñuel’s film Los Olvidados (Young and the damned) with Guillermo Fadanelli’s novel La otra cara de Rock Hudson to define and underline the characteristics of the space in which both pieces happen. The portrait of Mexico City made by the authors is cruel and miserable, and it demystifies what was once considered a sacred place yearned by its founders, ideal for a good future. This point of view has created a dangerous city stereotype that doesn’t seem to fade in the works of art that take place there. The monster city does not seem like a place that can be controlled.
Keywords: Luis Buñuel; Young and the damned; Guillermo Fadanelli; Compared literature; Mexico City